Peningkatan Pengelolaan Sarana Dan Prasarana Pendidikan Untuk Meningkatan Kualitas Pembelajaran Di SMP Negeri 9 Palangka Raya - Marni Marni; Dedy Norsandi; Yossita Wisman (Jurnal Ilmiah Kanderang Tingang, 2024)
Management of facilities and infrastructure is very important because by managing the facilities and infrastructure of educational institutions, their use will be maintained and clear. In managing the school, the school must be responsible for the facilities and infrastructure, especially the school principal who directly handles the facilities and infrastructure. And the school must be able to maintain and pay attention to existing school facilities and infrastructure. So, with the facilities and infrastructure in schools, students can learn optimally and as efficiently as possible. So the management of facilities and infrastructure must be emphasized even more in educational institutions such as schools. And someone must be responsible for managing the facilities and infrastructure. By managing the facilities and infrastructure in the school, the principal can plan and record what facilities and infrastructure must be used in the school. If all management steps have gone well as expected, it will have a positive impact on students in the teaching and learning process and achieving educational goals effectively and efficiently. So education administrators, whether the government, school principals, teachers, other school personnel or the community, need to continue to strive to improve the quality of education in line with the demands of the times.